Desalination Performance and Fouling Mechanism of Capacitive Deionization: Effects of Natural Organic Matter. Issue 4 (11th February 2020) - Wang, Tianyu; Liang, Heng; Bai, Langming; Liu, Bin; Zhu, Xuewu; Wang, Jinlong; Xing, Jiajian; Ren, Nanqi; Li, Guibai
Abstract : This article focuses on the capacitive deionization (CDI) performance and fouling mechanism during individual/combined fouling with natural organic matter (NOM). The desalination performance of CDI was significantly reduced in the presence of NOM and decreased as the NOM concentration increased. This was attributed to the fact that NOM deposition changed the adsorption site, resistance and capacitance characteristics of the electrode. The migration behaviors of NOM in the CDI system were studied by mass conservation, and the deposition of humic acid (HA) on the electrode was greater than that of bovine serum albumin (BSA). However, BSA induced more severe CDI fouling and caused a 40% reduction in the adsorption capacity of the CDI system, due to the different deposited morphologies on the electrode surface. Scanning electron microscopy (SEM) showed that HA was mainly adsorbed in the pores of the electrode, while BSA was deposited on the electrode surface in the form of obvious contamination spots due to agglomeration, resulting in a further decrease in the adsorption sites for CDI. In addition, compared to HA, the resistance of the CDI system fouled by BSA was increased by 25%, while the capacitance was reduced by 15%.